(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Introduction: Cerbrovascular Accidents (CVA’s) are a major burden over the society with highly associated mortality as well as mortality. Therefore it is important to find the markers which may help us in order to determine its prognosis. Objective: To determine the mortality rate and frequency of poor outcome among patients presenting with CVA along with the relation to higher and normal CRP levels obtained within 24 hours of the start of symptoms Material and Methods: This case-control study was conducted at Neurology department of Sir Ganga Ram Hospital/ Fatima Jinnah Medical University, Lahore. Total duration of study was 18 months, from January, 2015 to June, 2016. All the patients with CVA presenting in Emergency department of the hospital within 24 hours of start of symptoms were included in the study. Patients underwent CT scan to confirm the diagnosis of CVA. Their blood sample of 3 ml quantity was obtained for CRP levels. According to CRP level, they were dichotomized into 2 groups: ≥6 mg/L (Cases); <6 mg/L (Controls). They were re-assessed after 3 months of presentation using modified Rankin Scale (mRS) for morbidity and the mortality. All data were analyzed by SPSS version 20. Results: A total of 235 patients were included in the study. They were dichotomized into two groups according to CRP level and 156 patients were in control while 79 patients were in case group. The mean age of patients was found as 63.9 ± 10.9 years and 66.19 ± 12.01 years in both groups. The mRS score was assessed at 3- months follow up and it was found that the mortality occurred among 29 patients (18.5%) in patients in Cases group while in 9 patients (11.3%) in Control group (P = 0.156). Also poor outcome was found in 76 patients (48.7%) in Cases while in 26 patients (32.9%) in Control group (P = 0.020). Odd’s Ratio was calculated for poor outcome in both groups and it was found as 1.937 (1.101, 3.406) and 1.776 (0.795, 3.963) for mRS>2 and mortality respectively. Conclusion: We conclude that CRP level is an easily available test and if it is higher than normal in patients with CVA, it is associated with poor outcome and higher mortality. So we may use this test routinely in order to predict the morbidity of the disease.